Inovasi Pembuatan Pupuk Organik Berbahan Baku Tandan Kosong Kelapa Sawit dengan Bantuan Cacing Tanah (Lumbricus rubellus) - Aang Kuvaini (JURNAL CITRA WIDYA EDUKASI, 2020)
Organic fertilizers are environmentally friendly fertilizers made from natural ingredients so that the use of organic fertilizers does not pollute the environment and damage the soil. Oil Palm Empty Bunches (TKKS) is one of the wastes from palm oil processing which can be used as solid organic fertilizer. At present, the potential for utilizing TKKS as a raw material for making organic fertilizers is very large. This study aims to determine the technique of making organic fertilizers with basic ingredients of TKKS ﬁ bers and earthworms (Lumbricus rubellus), and find out the nutrient content contained in them. This research was carried out by an experimental method on an organic fertilizer maker or unit. Based on the results of the study, solid organic fertilizers can be made with basic TKKS ingredients and the decomposition process using earthworms (Lumbricus rubellus). In 100 grams of solid organic fertilizer produced containing nutrients namely Na dd (cmol/kg) (0.44), Total N (0.24%), P Total (mg P2O5/100g) (133.54%), Total K (mg K2O/100 g) (147.92), Mg (0.01), Za (55.62) and Fe (44.117).